Sensors and Biosensors Related to Magnetic Nanoparticles - Kurlyandskaya, Galina V. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book describes interesting examples of magnetic materials with magnetic nanoparticles or compact devices using composites with nanoparticles, including new engineering solutions and theoretical contributions on the magnetic biosensing of soft matter composites. Authors from different countries formed international team of experts sharing 10 contributed papers, 1 feature paper, and 1 topical review.